Strategi Penerimaan Murid Baru Berbasis Asesmen Daerah di Kota Yogyakarta - Sri Lestari Andayani; Nerys Lourensius (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study aims to analyze the regional assessment-based student admission strategy in Yogyakarta City, addressing the issues of unequal selection tools and unequal school distribution. The use of report card scores as a selection tool often does not consistently reflect student abilities across schools, while uneven distance zoning due to existing city design since the colonial era worsens the distribution of educational access. Some areas in Yogyakarta even become "blank spots" without public schools, adding to the challenges in educational equity. This study uses a qualitative approach with a literature review to explore the implementation of the Regional Education Standardization Assessment (ASPD) as a solution to create a more standardized and equitable selection tool. The ASPD is expected to address zoning inequality and provide more equal opportunities for prospective students, both from within and outside the Special Region of Yogyakarta (DIY). The implementation of this regional-based assessment also aims to maintain the quality of education in Yogyakarta, known as the city of education, so that it remains competitive at the national and international levels. The results show that with the implementation of ASPD, the selection process for new student admissions can be more objective and relevant to local conditions, while reducing the gap in educational quality. Thus, this regional assessment-based admission strategy is an important step to maintain the quality of education in Yogyakarta City.